KOMUNITAS IKAN SUKU CYPRINIDAE DI PERAIRAN SEKITAR BUKIT BATIKAP KAWASAN PEGUNUNGAN MULLER KALIMANTAN TENGAH [The Fish Community of Cyprinids from Bukit Batikap Waters in Muller Mountain Areas Central Kalimantan] - Haryono Haryono (Jurnal Iktiologi Indonesia, 2004)
This study was conducted in Joloi river (Barito sub-watershed) in province of Central Kalimantan. The aims of study are to know fish diversity, abundance, local distribution, species status, and its potency. The results were recorded 26 species from 15 genus, the range of abundance between 1-29,83; local distribution between 0,69-9,66%, 5 endemic species, 1 new record, most have potency as fish consume. The tambra fish require to be studied furthermore.